USE OF CANNABIS FOR MEDICINE (JHON FISKE SEMIOTIC ANALYSIS) - Fikri, M. Andi (Journal of Social Science, 2024)
Film is an integral part of mass communication, and in its purpose film itself as a message in conveying and offering more than just sound and meaningful images. Recently, the phenomenon of legalizing marijuana has often been discussed and constructed through the media. One of them is the documentary "Musa" by Alexander Sinaga on the YouTube channel LGN_ID TV. The aim of this research is to find out what the struggle of mothers in the use of marijuana for health means. This research uses John Fiske's semiotic analysis and qualitative methodology in a critical perspective. Based on reality patterns with codes of appearance, costume, expression, body movement, and language to the objectives of the research through the pattern of reality. The results of this study show the facts of the three mothers' struggle in the attempt to use marijuana for treatment in the documentary "Musa".